Strategi Penerapan Value Chain dalam Meningkatkan Competitive Advantage UMKM Kerajinan - Arif, Arif; Wibawa, Gian Riksa; Pauzy, Depy Muhamad (Ecoplan, 2025)
The craft industry requires creativity, skills, and talent to transform products into goods with economic value. In Rajapolah, the craft industry is expected to become a major contributor to both local and national economies. However, the intense competition and declining consumer interest in craft products pose significant challenges. Therefore, craft-based MSMEs need to find effective solutions to enhance their competitive advantage. This study aims to analyze the competitive advantage of craft MSMEs through the value chain approach. It tries to identify effective strategies for developing and expanding the creative economy of MSMEs in Rajapolah. This research adopted a qualitative approach. Primary data were collected through semi-structured interviews involving 15 creative MSME actors in Rajapolah. The interviews were conducted directly with business actors who process raw materials into finished products for both domestic and international markets. The findings indicate that the application of technology presents a significant opportunity for MSMEs to increase their competitiveness and expand their market reach. Digital technology, particularly in online sales systems, emerges as a key factor that should be maximized. Although several MSME producers have started using online sales channels, they have not yet optimized this potential. Therefore, more focused and strategic use of digital platforms is expected to open up broader marketing opportunities for Rajapolah craft MSMEs, allowing them to reach beyond local consumers and compete in wider markets.